A review of behavioral treatments for sleep disturbances in civilians who have experienced trauma. (27th December 2021) - Roche, Laura; McLay, Laurie; Sigafoos, Jeff; Whitcombe‐Dobbs, Sarah
Abstract: Sleep disturbances have frequently been associated with trauma and post‐traumatic stress disorder (PTSD). Effective treatments for sleep disturbances are therefore likely to be indicated for individuals who have experienced trauma. With the aim of advancing evidence‐based practice in this area, this review focuses on studies evaluating behavioral treatments for sleep disturbances among civilians who have experienced trauma. Seventeen studies were identified that met inclusion criteria. Data were extracted from each study on (a) the type of sleep disturbance experienced, (b) assessments used, (c) treatment procedures, (d) outcome measures, and (e) main findings. Research quality was also evaluated. The results of these 17 treatment studies were generally positive, but ratings of the strength of the research varied from strong to weak. Overall, this review finds evidence to support the use of behavioral treatments for sleep disturbances resulting from experiences of trauma. The implications of these findings for clinical practice are discussed.